The Dreamed up Community: Connections of the Family Members in the Traditional Dream Narratives - Ivanauskaitė-Šeibutienė, Vita (Tautosakos darbai, 2016)
The major part of the Lithuanian folkloric dream narratives consists of stories about family members or relatives seen in the dreams. The dream experience reflected in those stories transforms into varying texts, thus becoming an exceptional and especially relevant means of continuing or supporting the communication between close people. As repeatedly noted by various studies of oneiric tradition, dream narratives existing and thriving among members of individual families, relatives or, in broader terms, in the local communities, are created and passed on from one generation to another by means of joining together personal dream experiences and traditions existing in the community (or local cultural patterns). The subject of analysis in this article comprises bonds between blood relatives or spouses created and shifted by means of dream narratives. The dream narrators belonging to older generations usually shape their stories in accordance with the traditional norms and order of life in the community: they tell of dreaming about working or celebrating together with other family members, of various requests or instructions given by the dead relatives to the living ones. The author of the article pays special attention to the kind of emotions and actions inspired by dreams involving communication with the deceased family members in the narrators and their listeners. As a separate group, stories of mothers dreaming of their children are distinguished. The author deliberately chooses the concept of traditional dream narratives in order to emphasize folkloric rather than psychological approach to her study, as well as in order to better define the analyzed material, which in this case consists of stories told by elderly people recorded during fieldwork and texts from various printed sources. Research by Eric Robertson Dodds makes up the theoretical basis for the study.
Keywords: -